International Trade: Specifics and Prospects of Participation of Developed, Developing Countries and Countries with Economies in Transition - Anastasia O. Rudneva (Модернизация, инновация, развитие, 2017)
Purpose: to analyze participation in the international trade of the separate groups of the countries - developed, developing and also with a transitional economy. Not only the level of development of their economies, but also the economy type, ability of transformation in market economy is the cornerstone of division of the countries. Dynamics of indicators from 2000 for 2015 is considered. The particular emphasis is placed on asymmetric influence of crises that is connected, first of all, with distinctions in structure of the economies, presence and prevalence of an oil and gas component of export at the certain countries to which number it is also possible to carry Russia.Methods: the author uses wide methodology, including analysis, synthesis, scientific abstraction, temporary extrapolation, mathematicalstatistical and graphic methods.Results: the revealed trends of development allow to reveal the prospects of further speeding up of positions of so-called high-growth economies at preservation of the leading role of developed countries. At the same time the role of Russia, despite a high level of gas and oil in its export, increases that is confirmed by growth not only absolute, but also relative indicators.Conclusions and Relevance: the materials stated in the article represent not only scientific, but also practical interest as allow to estimate the prospects of participation in the international trade of actors of the various groups of countries taking into account the level of their economic development. The main countries drivers among the developed countries, developing countries and countries with economies in transition are defined; the main exporters and importers are revealed; the commodity structure of the world trade and the largest exporters are determined by various commodity positions; the commodity and geographical structure of the foreign trade of the developed, developing countries and countries with economies in transition is characterized for this purpose. Shift of the centers of influence towards the developing economies allows drawing conclusions on the level of the international competitiveness of their economies, however high sensitivity to the crises says about immaturity and need of further building of the hi-tech and service sector that it is more characteristic of the developed countries. Russia continues to take the central place among the countries with economies in transition, being focused in foreign trade on the EU and China. Structural disproportions in its national economy predetermine high sensitivity to pricing on power raw materials without which decrease speeding up of positions on the world scene is impossible.